Stochastic Expected Utility for Binary Choice: New Representations - Matthew Ryan (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2018)
We present new axiomatisations for various models of binary stochastic choice that may be characterised as "expected utility maximisation with noise". These include axiomatisations of strictly (Ryan 2018a) and simply (Tversky and Russo, 1969) scalable models, plus strict (Ryan, 2015) and strong (Debreu, 1958) Fechner models. Our axiomatisations complement the important contributions of Blavatskyy (2008) and Dagsvik (2008). Our representation theorems set all models on a common axiomatic foundation, progressively augmented by additional axioms necessary to characterise successively more restrictive models. In particular, we are able to decompose Blavatskyy's (2008) common consequence independence axiom into two parts: one that underwrites the linearity of utility and another than underwrites the Fechnerian structure of noise. This has signifcant advantages for testing the Fechnerian models, as we discuss.
Keywords: 330